Examining the role of personal innovativeness and trust in predicting generation Z’s online booking behaviour - Hapsari, Raditha; Sabil Husein, Ananda; Gan, Christopher (BISMA (Bisnis dan Manajemen), 2023)
This study responds to the Technological Acceptance Model (TAM) critics regarding the model's missing self-regulatory and motivational variables. The research integrates personal innovativeness and perceived risk in the TAM model and explores the interrelationships among those constructs. A self-administered questionnaire was used to collect the data for this study, and 293 consumers of the Indonesia Online Travel Agent (OTA) industry participated. The data were analysed using Partial Least Square, which employed the inner and outer model evaluations to analyse the data. The results demonstrated that Generation Z's attitude toward using the OTA application is positively affected by its perceived usefulness and ease of use. Moreover, three variables significantly affect Generation Z's behavioural intention to use e-commerce applications. Personal innovativeness significantly affects perceived transaction risks and attitudes toward using the OTA application. These results imply that in order to enhance customers’ willingness to keep using the application, the OTA practitioners should ensure that their customers experiencing the ease-of-use dan the usefulness of the application, so that the customers will have a greater willingness to use the same application in the future.